Geochemical and hydroclimatic constraints on the formation of borate deposits in Da Qaidam Salt Lake of Qaidam Basin, northern Tibetan Plateau. Issue 4 (March 2020) - Gao, Chunliang; Yu, Junqing; Min, Xiuyun; Cheng, Aiying
Abstract: The pinnoite deposit occurred in the lakebed of Da Qaidam Salt Lake in Qaidam Basin is rare in the world. This study focused on the pinnoite, ulexite and hydroboracite from Da Qaidam Salt Lake, through multi-index methods including mineralogy and geochemistry, aiming to interpret the mechanism of pinnoite and other borate minerals. The results showed that pinnoite as well as ulexite and hydroboracite in lakeside are formed in the lake environment with specific hydrogeochemical conditions (e.g., alkaline brine, hydrochemical types, boron concentration, boron ions, Mg/Ca ratio, dilution and mixing mechanism). The borate formation was controlled by a coupling mechanism, i.e., the inherent geochemical characteristics and the external conditions.